The Impact of Alcohol-Induced Epigenetic Modifications in the Treatment of Alcohol use Disorders - Fanfarillo, Francesca; Ferraguti, Giampiero; Lucarelli, Marco; Fuso, Andrea; Ceccanti, Mauro; Terracina, Sergio; Micangeli, Ginevra; Tarani, Luigi; Fiore, Marco (Current Medicinal Chemistry, 2024)
Alcohol use disorders are responsible for 5.9% of all death annually and 5.1% of the global disease burden. It has been suggested that alcohol abuse can modify gene expression through epigenetic processes, namely DNA and histone methylation, histone acetylation, and microRNA expression. The alcohol influence on epigenetic mechanisms leads to molecular adaptation of a wide number of brain circuits, including the hypothalamus-hypophysis-adrenal axis, the prefrontal cortex, the mesolimbic-dopamine pathways and the endogenous opioid pathways. Epigenetic regulation represents an important level of alcohol-induced molecular adaptation in the brain. It has been demonstrated that acute and chronic alcohol exposure can induce opposite modifications in epigenetic mechanisms: acute alcohol exposure increases histone acetylation, decreases histone methylation and inhibits DNA methyltransferase activity, while chronic alcohol exposure induces hypermethylation of DNA. Some studies investigated the chromatin status during the withdrawal period and the craving period and showed that craving was associated with low methylation status, while the withdrawal period was associated with elevated activity of histone deacetylase and decreased histone acetylation. Given the effects exerted by ethanol consumption on epigenetic mechanisms, chromatin structure modifiers, such as histone deacetylase inhibitors and DNA methyltransferase inhibitors, might represent a new potential strategy to treat alcohol use disorder. Further investigations on molecular modifications induced by ethanol might be helpful to develop new therapies for alcoholism and drug addiction targeting epigenetic processes.
Keywords: AUD